Analisis Keterampilan Pukulan Gyaku Tsuki Dalam Kumite Pada Atlet Karate Jambi Menggunakan Video Dartfish - Joka Novetra; Rizki Kurniati; Sri Murniati; Danang Pujo Broto (Jurnal Keolahragaan, 2026)
This study aimed to analyze the technical proficiency of the Gyaku Tsuki punch during kumite among karate athletes at Jambi Karate Club (JKC) using Dartfish video analysis. A quantitative descriptive observational design was applied. The population comprised all competitive athletes observed in the study setting, and total sampling was used, resulting in six athletes (n=6). Data were collected through video-recorded kumite bouts and an observation checklist that decomposed Gyaku Tsuki into 20 key performance indicators: guard readiness, stance execution and transition, body alignment and stability, hip rotation, punching trajectory, elbow extension, target direction (chudan), gaze control, and recovery to guard. Each item was scored dichotomously (correct=1; incorrect=0) and summed into a 0–20 total score, then classified using predefined norm intervals. Data were analyzed using descriptive statistics and percentage distributions. Results showed that 2 athletes (33.33%) achieved a “very good” category (17–20) and 4 athletes (66.67%) achieved a “good” category (13–16), with no athletes in moderate, poor, or very poor categories. In conclusion, overall Gyaku Tsuki execution during kumite was good, yet targeted technical refinement and pressure-specific practice are recommended to improve consistency and scoring effectiveness. Keywords: karate; kumite; gyaku tsuki; technique analysis; Dartfish